2021
DOI: 10.1002/zaac.202000400
|View full text |Cite
|
Sign up to set email alerts
|

Mastering extreme size constraints in the clathrate‐I borosilicide Cs8B8Si38

Abstract: Cs8B8Si38 is obtained by high‐pressure high‐temperature synthesis at p=8 GPa and T=1273 K. The new compound (space group Pm3‾ n; a=10.0312(3) Å) is the third example for a clathrate‐I borosilicide after the potassium and rubidium varieties, respectively. The phase slowly deteriorates in air and moisture but is thermally stable up to 1050 K at ambient pressure. [Cs+]8[B–]8[Si0]38 is electronically balanced, diamagnetic, and shows semiconducting behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…It is interesting to compare the boron substitution trends for carbon clathrates with those of the substitutions observed for silicon clathrate frameworks. In contrast with the type-I carbon clathrates here, previous studies have found that the 16 i site is preferable for boron substitution in type-I silicon clathrates (e.g., K 7 B 7 Si 39 ). The occupation of 16 i , which is exclusively located in pentagonal rings, helps relieve bond strain caused by the large disparity in B–Si and Si–Si bond distances . For type-I silicon clathrates with Al substitutions, e.g., Ba 8 Al x Si 46– x , the occupation of the 6 c and 24 k sites are favorable for Al atoms at small (e.g., x = 8) and large (e.g., x = 15) bulk Al concentrations, respectively. , Al substitution in type-I silicon clathrates is similar to the trends observed here for B substitution in type-I carbon clathrates.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…It is interesting to compare the boron substitution trends for carbon clathrates with those of the substitutions observed for silicon clathrate frameworks. In contrast with the type-I carbon clathrates here, previous studies have found that the 16 i site is preferable for boron substitution in type-I silicon clathrates (e.g., K 7 B 7 Si 39 ). The occupation of 16 i , which is exclusively located in pentagonal rings, helps relieve bond strain caused by the large disparity in B–Si and Si–Si bond distances . For type-I silicon clathrates with Al substitutions, e.g., Ba 8 Al x Si 46– x , the occupation of the 6 c and 24 k sites are favorable for Al atoms at small (e.g., x = 8) and large (e.g., x = 15) bulk Al concentrations, respectively. , Al substitution in type-I silicon clathrates is similar to the trends observed here for B substitution in type-I carbon clathrates.…”
Section: Resultsmentioning
confidence: 64%
“…83−85 The occupation of 16i, which is exclusively located in pentagonal rings, helps relieve bond strain caused by the large disparity in B−Si and Si−Si bond distances. 84 For type-I silicon clathrates with Al substitutions, e.g., Ba 8 Al x Si 46−x , the occupation of the 6c and 24k sites are favorable for Al atoms at small (e.g., x = 8) and large (e.g., x = 15) bulk Al concentrations, respectively. 86,87 Al substitution in type-I silicon clathrates is similar to the trends observed here for B substitution in type-I carbon clathrates.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
“…In the course of this work, several other Rb- and Cs-containing compounds (not just antimonides) not included in the original machine learning data set were discovered and their structures were experimentally determined: (i) channel structures for ATrSb 4 (A = Rb or Cs; Tr = Al or Ga); (ii) layered structures for ATrSb (A = Rb or Cs; Tr = Cd or Zn), Rb 2 Mo 2 As 3 , CsGa 6.05 In 0.95 , and RbGa 6.31 In 0.69 ; (iii) clathrate structures for A 8 Ga 27 Sb 19 (A = Rb or Cs), Cs 8 In 27 Sb 29 , Rb 4 Si 19 B 4 , Cs 4 Si 19 B 4 , and Cs 4 Ga 3.75 Sn 19.25 ; and (iv) network structures for Rb 3 Ga 12.32 In 0.68 and Rb 3 Hg 0.42 Ga 12.58 . All of these structures are in good agreement with those of the SISSO-derived models (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…27 Hu ¨bner et al synthesized two semiconductors: Rb 8 B 8 Si 38 with moderate thermoelectric properties 28 and Cs 8 B 8 Si 38 with fairly good thermal stability. 29 In contrast, we conducted theoretical investigations on ternary alkali metal borosilicides with the formula AB 3 Si 3 (A = Na/K/Rb/Cs), 30 which is isomorphic to the aforementioned SrB 3 C 3 compound. 15 RbB 3 Si 3 can be quenched under ambient conditions and possess superconductivity with a T c value of 14 K. 30 However, the novel physical phenomena of non-clathrate AB 3 Si 3 (A = Na/K/Rb/Cs) compounds under high pressure, including the rich phase diagram, stability, and tunable electronic properties, are still largely unknown, despite their important role in the field of new materials.…”
Section: Introductionmentioning
confidence: 99%